A new and highest record of Tylototriton notialis (Amphibia: Urodela: Salamandridae) - Nishikawa, Kanto; Sanamxay, Daosavanh; Kurita, Takaki; Hibino, Masatoshi; Jono, Teppei; Tao, Nguyen Thien (Academia Journal of Biology, 2020)
Short Communications